Hierarchical Self‐Assembly of Dopamine into Patterned Structures. Issue 11 (8th March 2017) - Zhang, Peibin; Tang, Anqi; Zhu, Baoku; Zhu, Liping; Zeng, Hongbo
Abstract : It has been demonstrated that dopamine can undergo oxidation and complicated self‐reaction in aqueous solution to form so‐called polydopamine (PDA). In this paper, for the first time, the hierarchical self‐assembly of dopamine into surface patterned structures is described. PDA nanoaggregates are first prepared assisted by ethylenediamine, based on the covalent self‐polymerization and noncovalent self‐assembly. The surface fractal patterns are further created and modulated by the dynamic self‐assembly of PDA nanoaggregates to develop more macroscopic ordered structure of PDA. Various surface patterns of PDA aggregates are successfully obtained by evaporative dewetting method. The effects of solution pH, type of inorganic salts, and temperature on the morphology of surface pattern are investigated. Mineralization or metal deposition is used to keep the pattern fixed. The surface patterning strategy reported here is applicable to a broad range of materials, which allows the developments of materials with controllable patterned structure. Abstract : The hierarchical self‐assembly of dopamine (DA) into patterned structure is reported for the first time. The process consists of static self‐assembly from DA to polydopamine (PDA) and dynamic self‐assembly from PDA into higher level aggregation morphologies via evaporative drying method. Moreover, the surface can be further functionalized, which brings a new insight in preparation of functional patterned surface.